ANALYSIS OF THE PROFESSIONAL COMPETENCES OF POSTAL OPERATORS - Kaitanovska Olha (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология, 2023)
The article analyzes the standard of professional (vocational and technical) education in the profession of postal operator with the aim of establishing their compliance with the modern requirements of employers and determining the modern structure of their professional competence. The purpose of the article is to analyze the standard of professional (vocational and technical) education in the profession of postal operator, to establish the correspondence of the description of the profession with the modern requirements of employers and to determine the modern structure of the professional competence of postal operators. In the process of research, the author used content analysis of regulatory and legal documents and reporting documentation, analysis of scientific and professional literature, the method of paired comparisons for expert assessment of modern competencies, and synthesis for generalization of the obtained results. A comparative analysis of the content of the modules according to the qualifications of each class was carried out. According to the results of the research, the necessity to transform the professional competence of future postal operators, who acquire a profession in professional (vocational and technical) education institutions, has been updated, which will correspond to the trend of rapid introduction of digital technologies into the activities of the postal infrastructure. Taking into account the current trends of rapid transformation of the field of postal communication, based on the results of the analysis of professional competencies of qualified workers of various professions, the websites of JSC Ukrposhta and the company Nova Poshta, the most relevant and necessary competencies for postal operators have been identified. It has been found out that there have been changes in the practical activities of postal operators, which have led to the expansion and transformation of the functions of postal operators. This has made it necessary to update the professional competence of postal operators, its structure and component composition, which must meet the requirements of the National Framework of Qualifications and its descriptors. Based on the analysis of specialized literature and reporting documentation of the most powerful domestic postal operators, a number of professional competencies is proposed: operational, programmatic, reference and informational, interpersonal, financial, statistical, communicative, foreign language, cultural and linguistic. Taking into consideration the results of the discussion with teaching staff of professional (vocational and technical) education institutions that train qualified workers in this profession, expert evaluation by a group of experts consisting of scientists, teachers of special disciplines, and representatives of employers, it was found out that the most important professional competencies of postal operators include operational, programmatic and communicative ones. The structure of professional competence of postal operators is defined, which consists of interconnected components: cognitive (including: knowledge that a qualified worker of this profession should possess: reference and information, financial, technical and technological, normative and legal, etc.), operational (containing a number of such competencies as: operational, programmatic, and financial ones), personal and valuable (representing a set of personal and professional qualities of a future qualified worker, their motivational orientation; the ability to understand themselves and others, a high level of responsibility towards themselves and clients, interpersonal, communicative, cultural and linguistic, and social-psychological competences).